2023
DOI: 10.3390/ijms24043078
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Electron Structure and Antimicrobial Properties of Mandelic Acid and Its Alkali Metal Salts

Abstract: This article investigated the structure, and the spectroscopic and antimicrobial properties of mandelic acid and its alkali metal salts. The electron charge distribution and aromaticity in the analyzed molecules were investigated using molecular spectroscopy methods (FT-IR, FT-Raman, 1H NMR, and 13C NMR) and theoretical calculations (structure, NBO, HOMO, LUMO, energy descriptors, and theoretical IR and NMR spectra). The B3LYP/6-311++G(d,p) method was used in the calculations. The antimicrobial activities of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Studies on the antimicrobial activity of mandelic acid (Hman) revealed that the minimum inhibitory concentration (MIC) required to inhibit the growth of S. aureus and E. coli strains fell within the range of 0.18-0.23% [43,74]. In the case of crystalline powder tests of (1), the mandelic ligand content in the suspension of the studied sample was 0.013%, 0.034%, 0.069%, and 0.14% for concentrations of 2%, 5%, 10%, and 20% (w/v), respectively.…”
Section: Antimicrobial Activity Of (1) and Its Composite Pmma + (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the antimicrobial activity of mandelic acid (Hman) revealed that the minimum inhibitory concentration (MIC) required to inhibit the growth of S. aureus and E. coli strains fell within the range of 0.18-0.23% [43,74]. In the case of crystalline powder tests of (1), the mandelic ligand content in the suspension of the studied sample was 0.013%, 0.034%, 0.069%, and 0.14% for concentrations of 2%, 5%, 10%, and 20% (w/v), respectively.…”
Section: Antimicrobial Activity Of (1) and Its Composite Pmma + (1)mentioning
confidence: 99%
“…Previous research regarding mandelic acid properties showed that prolonged skin exposure to Hman absorption may lead to redness, dryness, and excessive skin exfoliation [41,42]. Hence, investigations carried out in recent years has focused on the synthesis and evaluation of the biocidal action of Hman salts and their complex compounds [43,44]. The compounds synthesized in the reaction of titanium isopropoxide with mixtures of mandelic and benzohydroxamic acid [45] or mandelic and phenylphosphonic acid [46] typically form dimeric structures, wherein two titanium atoms ({Ti 2 }) are connected solely by mandelic ligands (man).…”
Section: Introductionmentioning
confidence: 99%
“…Bismerthiazol and thiadiazole copper are widely utilized bactericides that have demonstrated efficacy in efficiently managing citrus canker . Mandelic acid, an α-amino acid, possesses significant antibacterial properties and is regarded as a promising substrate and intermediary for the development and synthesis of innovative drugs. , The utilization of mandelic acid and its derivatives is prevalent in the fields of medicines, aesthetic medicine, and environmental therapy. , Furthermore, there have been reports in the field of agriculture indicating that they possess the ability to effectively minimize the occurrence of black shank . Although all of the aforementioned compounds possess antiseptic properties, it is possible to develop and synthesize their active structural frameworks using novel methodologies in order to acquire the desired molecules.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 The utilization of mandelic acid and its derivatives is prevalent in the fields of medicines, aesthetic medicine, and environmental therapy. 38,39 Furthermore, there have been reports in the field of agriculture indicating that they possess the ability to effectively minimize the occurrence of black shank. 40 Although all of the aforementioned compounds possess antiseptic properties, it is possible to develop and synthesize their active structural frameworks using novel methodologies in order to acquire the desired molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on mandelic acid properties showed that prolonged skin exposure to Hman absorption may lead to redness, dryness, and excessive skin exfoliation [41,42]. Hence, investigations carried out in last years, focused on the synthesis and the evaluation of the biocidal action of Hman salts and their complex compounds [43,44]. The compounds synthesized in the reaction of titanium isopropoxide with mixtures of mandelic and benzohydroxamic acid [45] or mandelic and phenylphosphonic acid [46] typically form dimeric structures, wherein two titanium atoms ({Ti2}) are connected solely by mandelic ligands (man).…”
Section: Introductionmentioning
confidence: 99%